Labeling tumor-associated extracellular vesicles with antibody-DNA conjugates for quantitative analysis - Xiao Du; Xiao Du; Xiao Du; Hongxiu Li; Hongxiu Li; Hongxiu Li; Shiyi Shen; Shiyi Shen; Shiyi Shen; Chao Tian; Chao Tian; Chao Tian; et al. (Frontiers in Molecular Biosciences)
IntroductionExtracellular vesicles (EVs) shed from tumor cells into peripheral circulation or other body fluids are promising biomarkers for cancer diagnosis with enormously long circulation. Consequently, precise methods for differentiating normal and tumor-associated EVs (TAEs) are required.MethodsThis study used quantifiable antibody-DNA conjugate-assisted quantitative methods combined with proximity ligation technology to detect TAEs. The antibody-DNA conjugate contained one antibody associated with three oligonucleotides for signal amplification. The antibody in the conjugate can recognize the surface tumor antigens of TAEs. Simultaneously, DNA in the conjugate is attached to the surfaces of TAEs and holds the signal amplification post, converting protein identities to DNA amplification for protein detection, even at the molecular level.ResultsThese findings revealed that TAEs can be quantitatively detected using DNA-mediated quantitative polymerase chain reaction (qPCR). Antibody-DNA conjugates were used to recognize the epithelial cell adhesion molecule (EpCAM) antigen on the TAE surface and quantify the antigen using qPCR for cancer analysis.DiscussionThis method proposed a new quantitative detection approach for TAEs, which aim to identify specific EV-associated markers for diagnostic or therapeutic, this method could inspire a new idea for tumor diagnosis and detection of other diseases.